2014
DOI: 10.3991/ijep.v4i2.3481
|View full text |Cite
|
Sign up to set email alerts
|

Online Experimentation in Education and Training

Abstract: The increasing use of emergent technologies in industry, medicine, research, training and education attests to the relevance of their integration in teaching/learning approaches. Online experimentation comprises remote and virtual experimentation also supported and complemented by other online tools that incorporate necessarily the use of emergent technologies. The present work synthesizes the final outcomes of a project aiming to develop, use and disseminate Online Experimentation, funded by the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Studies have shown that case studies are an effective way to help students learn in an online environment. [7][8][9] [28] This ensured that the student had a grasp on the theoretical part of the subject and could apply it too.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that case studies are an effective way to help students learn in an online environment. [7][8][9] [28] This ensured that the student had a grasp on the theoretical part of the subject and could apply it too.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning IoT Abraham [3] did a project and survey in which they established IoT connections with the sensor data of the participating students' cellphones, whereas Cvjetkovic [4] developed an IoT project connected with Pocket Labs. Restivo and Cardoso [5] investigated the integration of AR and Virtual Reality (VR) into engineering education with several projects like an electrical circuit using AR, whereas the work of Elsaadany and Soliman [6] inquiries the alternate points of view of students, instructors and learning executives on IoT. They argue that IoT can transform the educational environment because of the increasing amount of accessible connected devices, which will lead to changes in students' and educators' behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Nine online learning courses with remote and virtual experiments were developed as a part of European lifelong program Leonardo da Vinci [7]. Hereby the years-long experience from developing of online education resources for regular university education was used to develop the education resources also for non-traditional learners [2], [5], [11].…”
Section: Introductionmentioning
confidence: 99%